Del milagro fonético a la catarsis judía: ecos de Artaud en La bucanera de Pernambuco o Hilda la polígrafa - Valentina Litvan (Cuadernos LIRICO)
This article proposes a reading of La bucanera de Pernambuco o Hilda la polígrafa from the notion of phonetic explosion. In this sense, an association is established with Antonin Artaud, whose last poetry was described as a phonetic miracle. The hypothesis is that with the phonetic outburst Pizarnik’s jewishness is also revealed. In the analysis, Pizarnik’s manuscripts are fundamental, and in particular her reading notes while being in Paris, and an unpublished text initially conceived to be part of La bucanera.